Pengaruh Struktur Modal, Profitabilitas, Dan Price To Book Value Terhadap Harga Saham - Achmalia, Nurul; Menik Indrati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The purpose of this research is to analyze the correlation between capital structure, profitability, and stock market value, proxied by the price-to-book ratio. The capital structure variable is measured using DER, while profitability is measured using the ROA. In this study, the data used comes from the financial statements of property and real estate companies listed on the IDX during the period of 2020 to 2023. This study applies multiple linear regression analysis with the help of SPSS to process data obtained from 22 purposively selected companies over four years. The research concludes that capital structure and profitability are crucial factors that can influence stock prices. These results indicate that companies need to focus on improving profitability and maintaining healthy debt management to enhance their value in the eyes of investors. Additionally, investors should not rely solely on the PBV when evaluating investment prospects.